2010
DOI: 10.21248/fvss.13.11
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions, mode de gestion et végétation des bois sacrés au nord du Burkina Faso

Abstract: L’étude s’inscrit dans le cadre de la valorisation des bois sacrés dans un contexte de conservation de la biodiversité, elle a pour objectifs de recenser les différents bois sacrés au nord du Burkina Faso, d’évaluer leur richesse floristique et d’appréhender leurs mécanismes de gestion par les populations locales. Des prospections ont été conduites sur l’ensemble de la zone d’étude en vue de recenser les bois sacrés. Dans chaque localité des enquêtes ont été conduites auprès des populations directement ou indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Violation of these prohibitions carries penalties that vary according to the seriousness of the offence. In the same vein, Savadogo et al (2010Savadogo et al ( , 2011) describe an endogenous management system for the natural resources of the sacred groves of the Mossi people of Burkina Faso, based on customary principles, rules and laws: no cutting of wood, no fires, no hunting, and no use of the grove outside days of worship. However, people's compliance with these principles and rules is declining, as this study has shown.…”
Section: Discussionmentioning
confidence: 99%
“…Violation of these prohibitions carries penalties that vary according to the seriousness of the offence. In the same vein, Savadogo et al (2010Savadogo et al ( , 2011) describe an endogenous management system for the natural resources of the sacred groves of the Mossi people of Burkina Faso, based on customary principles, rules and laws: no cutting of wood, no fires, no hunting, and no use of the grove outside days of worship. However, people's compliance with these principles and rules is declining, as this study has shown.…”
Section: Discussionmentioning
confidence: 99%